2023
DOI: 10.1021/acsnano.3c06564
|View full text |Cite
|
Sign up to set email alerts
|

Inspired Beyond Nature: Three Decades of Spherical Nucleic Acids and Colloidal Crystal Engineering with DNA

Abstract: The conception, synthesis, and invention of a nanostructure, now known as the spherical nucleic acid, or SNA, in 1996 marked the advent of a new field of chemistry. Over the past three decades, the SNA and its analogous anisotropic equivalents have provided an avenue for us to think about some of the most fundamental concepts in chemistry in new ways and led to technologies that are significantly impacting fields from medicine to materials science. A prime example is colloidal crystal engineering with DNA, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 201 publications
0
10
0
Order By: Relevance
“…Owing to their unique three-dimensional structure and highly programmable assembly, SNAs exhibit a range of distinctive physicochemical properties, including reduced degradation risk in the presence of nucleases, efficient transfection of various tissues and cells, and good immunogenicity. 18–21 As an innovative nucleic acid delivery system, SNAs possess immense potential as universal transportation nanoplatforms for nucleic acids, drugs, and proteins, with enhanced clinical translation prospects in biomedical applications; therefore, there have been many reviews with a focus on this hot subject of research. For example, Jiang et al presented thorough elucidation of the selection process concerning the core and densely organized DNA shells within SNAs, and further introduced the applications of SNAs in disease diagnosis and treatment, encompassing in vitro biosensing, intracellular assessment, gene regulation, drug delivery, and immune modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their unique three-dimensional structure and highly programmable assembly, SNAs exhibit a range of distinctive physicochemical properties, including reduced degradation risk in the presence of nucleases, efficient transfection of various tissues and cells, and good immunogenicity. 18–21 As an innovative nucleic acid delivery system, SNAs possess immense potential as universal transportation nanoplatforms for nucleic acids, drugs, and proteins, with enhanced clinical translation prospects in biomedical applications; therefore, there have been many reviews with a focus on this hot subject of research. For example, Jiang et al presented thorough elucidation of the selection process concerning the core and densely organized DNA shells within SNAs, and further introduced the applications of SNAs in disease diagnosis and treatment, encompassing in vitro biosensing, intracellular assessment, gene regulation, drug delivery, and immune modulation.…”
Section: Introductionmentioning
confidence: 99%
“…With oligonucleotides, this concept was first realized by immobilization of thiol-functionalized strands onto gold nanoparticles, giving rise to a spherical nucleic acid. 63,64 A metal core is not indispensable, however, and more recently spherical nucleic acids have also been synthesized with various non-metallic cores, such as fullerene or cubic silsesquioxane. 65 Even completely coreless ones have been prepared by dissolving the gold nanoparticle core after assembly of the spherical nucleic acid and cross-linking the constituent strands.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, research on self-assembly has resulted in a suite of nanoscale building blocks capable of achieving long-range structural ordering at the mesoscale. 40,44,45 This toolkit spans a diverse range of techniques that include surface modifications, 46–50 emulsion-templating, 51 solvent evaporation, 52,53 and microphase separation. 54,55 Amongst this expansive library, shape anisotropy and nanoparticle (NP) ligand functionalization have emerged as two popular strategies that are now widely used for controlling assembly.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been excellent reviews that cover both synthesis and experimentally observed assemblies of LNPs. 40,44,45,57,58 As such, we refer the reader to those works for current experimental advances.…”
Section: Introductionmentioning
confidence: 99%